Faktor-Faktor yang Memengaruhi Niat Mengundurkan Diri Karyawan Generasi Y di Indonesia - Amelia Suryaputri; Annisa Damayanti; Dionisius Waskita Waskita; Mohammad Edwin Irawan; Rizyantana Irawan; Achmad Setyo Hadi (Indonesian Business Review, 2021)
This study aims to identify the relationship between organizational justice, supervisory justice, authoritarian organizational culture, organization-employee relationship quality, and work engagement with the turnover intention of generation Y employees. An online survey was conducted on 290 people in Indonesia. Survey responses were recorded using a Likert Scale with a scale ranging from 1 (strongly disagree) to 7 (strongly agree). The results of the survey analysis were obtained by using regression to predict the relationship between the independent and dependent variables. The results showed that the variable which has a positive relationship with the turnover intention in generation Y employees is authoritarian organizational culture. As for the organization-employee relationship quality variable shows importance because it has the most significant relationship to retain generation Y employees. The research contributes to the previous research on determinants of employee turnover intention in that it is adding the work engagement variable as a new determinant of the turnover intention of generation Y employees.